2000
DOI: 10.1046/j.1523-1739.2000.99283.x
|View full text |Cite
|
Sign up to set email alerts
|

Population Persistence and Offspring Fitness in the Rare BellflowerCampanula cervicariain Relation to Population Size and Habitat Quality

Abstract: Data from several animal species and a few plant species indicate that small populations face an elevated risk of extinction. Plants are still underrepresented in these studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 53 publications
1
29
1
Order By: Relevance
“…Thirdly, Oostermeijer et al (1996), Ågren (1996) and Eisto et al (2000) have shown that a reduced individual fitness does not necessarily im- (Table 5, Fig. 5).…”
Section: Fragmentation Extinctions and Colonizationmentioning
confidence: 92%
“…Thirdly, Oostermeijer et al (1996), Ågren (1996) and Eisto et al (2000) have shown that a reduced individual fitness does not necessarily im- (Table 5, Fig. 5).…”
Section: Fragmentation Extinctions and Colonizationmentioning
confidence: 92%
“…EISTO et al 2000, VERGEER et al 2003. Moreover habitat quality may also be the key factor affecting plant performance.…”
Section: Effects Of Environmental Variablesmentioning
confidence: 99%
“…However, our results are in concordance with observations of Eisto et al (2000) who have reported that population size in the perennial herb Campanula cervicarea) had no effect on its seed germination or seedling growth.…”
Section: Berteroisupporting
confidence: 93%